Early Childhood Caries Assessment and Related Risk Factors among a Group of Lebanese Preschool Children: A Cross-Sectional Study - Ahmad Tarabaih
Objective: The study aimed to assess the prevalence of Early Child Caries and its associated risk factors among a group of Lebanese preschool children. Materials and Methods: An observational, cross-sectional study design that included 388 children recruited from different schools in Beirut, Lebanon. The parents were interviewed to answer a questionnaire developed by the World Health Organization (WHO, 1997) and Caries Assessment Risk tool developed by the American Academy of Pediatric Dentistry (AAPD, 2019). Then, caries prevalence was assessed by examining the children using the WHO decayed, missed or filled primary teeth (dmft) index and the rating scores of dental caries were classified as very low <1.2, low 1.2 - 2.6, moderate 2.7 - 4.4 and high 4.4 (WHO, 1997). Results: The mean age of the children was 4.03 ± 0.82 years. The prevalence of ECC was 71.1% and the mean dmft index was noted to be 3.11 ± 3.67. Based on the risk assessment results, 68% of the preschool children had high caries risk whereas 32% had low caries risk. A statistically significant differences in mean dmft scores were noted in which 3-years-old children exhibited a lower mean dmft value compared to 4 and 5 years olds (p<0.001). In addition, a significant difference was also found in dmft scores between middle socioeconomic status (SES) schools and low SES schools (p=0.016). Conclusion: Oral health promotion programs are to be implemented on regular basis to enhance the oral health status and general well-being of young children.